"Digital petrophysics" in studies of porosity properties of low- permeable reservoirs - Ponomarev A. A.; Zavatsky M. D.; Veduta O. V.; Shulga R. S.; Vyatkina K. O.; Koryashov I. A. Iliya Aleksandrovich (Latest Research in Reservoir Engineering, 2016)
Title screen